Development of a Web-Based Guidance and Counseling Information System for Students at SMA N 5 Pematang Siantar - rahmat raihan harahap; Asiah (Insight: Journal of Counseling and Psychology, 2026)
This study aims to develop a web-based guidance and counseling information system for students at SMAN 5 Pematang Siantar. The study uses the 4D development model, which consists of the define, design, development, and disseminate stages. The subjects in the product trial consisted of 30 students, one media design expert, one practitioner (counseling teacher), and one counseling teacher as the questionnaire respondent. The instruments used included an expert validation sheet, a teacher response questionnaire, and a student response questionnaire. The validation results showed a score of 92% from the design expert, 87% from the practitioner, 88% from the guidance counselor, and 89.4% from the student response, all of which were in the “very feasible” category. The response questionnaire was also tested for validity using the Pearson correlation technique to ensure the quality of the items. The developed system was assessed as effective in supporting the implementation of guidance and counseling services in schools, such as scheduling, individual and group consultations, and career services. This application contributes to ease of access, service effectiveness, and increased student participation in digital-based guidance and counseling services. In addition, this system also has the potential to be implemented more widely in other schools as an adaptive guidance and counseling service innovation in line with developments in educational technology.